The Limits of Minsky's Financial Instability Hypothesis as an Explanation of the Crisis - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
The financial crisis has been widely interpreted as a Minsky crisis. This paper argues that interpretation is misleading. The processes identified in Minsky's financial instability hypothesis played a critical role in the crisis, but that role was part of a larger economic drama involving the neoliberal growth model. The neoliberal model inaugurated an era of wage stagnation. In place of wage growth spurring demand growth, it relied on borrowing and asset price inflation. That arrangement was always unsustainable but financial innovation and deregulation warded off the model's stagnationist tendencies far longer than expected. These delay mechanisms is where Minsky's financial instability hypothesis enters the narrative. The interpretation of the financial crisis and Great Recession has enormous significance for economic policy. If interpreted as a purely financial crisis, in the spirit of a pure Minsky crisis, the policy implication is simply to fix the financial system. However, there is no need for reform of the real economy because that is not the source of the problem. If instead, the crisis is interpreted through a new Marxist - Structural Keynesian lens the policy implications are deeper and more challenging. Financial sector reform remains needed to deal with the problems of destabilizing speculation and political capture. However, it does not address the root problem which is the neo-liberal growth model. Restoring stable shared prosperity requires replacing the neoliberal model with a new model that restores the link between wage and productivity growth. That will require adoption of a new labor market agenda, re-fashioning globalization, reversing the imbalance between market and government, and restoring the goal of full employment. Financial sector reform without reform of the neoliberal growth model will leave the economy stuck in an era of stagnation. That is because stagnation is the logical next step of the neoliberal model given current conditions. Ironically, financial sector reform alone may worsen stagnation since financial excess was a major driver of the neoliberal model and that driver would be removed.
urn:nbn:de:101:1-201101312750
Keywords: 330